Research on Service Life Prediction Model of Thrust Needle Bearing - Hu Zhanqi; Qi Xiaowen; Fan Bingli; Li Wei (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
Needle roller thrust bear is small in size and of high ability in load bearing, therefore it is widely used in fields of aviation and automobile etc.  But the relation between their service life and pre-tightening torque is not very clear, so the using design of the bear depends mainly on experience of engineer, because of lack of references. In the paper, the theoretical analysis on relation between torque and load is done, special wearing test instrument is developed and wearing test of thrust needle bear is conducted. Based on the results of the test, mathematical model of relation between the losing amount of pre-tightening torque and the pre-tightening torque is built, based on which use of the bear in engineering will be more reasonable, and their pre-tightening torque will be given more accurately. DOI: http://dx.doi.org/10.11591/telkomnika.v10i7.1553